2001
DOI: 10.1007/bf03343837
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender specific stimulation of creatine kinase specific activity by gonadal steroids in human bone-derived cells in culture

Abstract: We previously reported a non-enzymatic method for isolation of human bone cells in culture that display osteoblastic features and respond to 1,25 dihydroxy vitamin D (1,25) and to parathyroid hormone (PTH). The present study was undertaken to analyze the response of cultured human bone cells to 17beta-estradiol (E2) and to dihydrotestosterone (DHT) as a function of gender and age. Cultured human bone cells, obtained from biopsies during orthopedic surgery, were divided into four groups defined by gender and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 33 publications
2
62
0
Order By: Relevance
“…1B). Therefore, these easily obtained and well characterized osteoblast cultures can be made estrogen responsive in vitro, replicating the hormone-sensitive status of osteoblasts that occur in more mature organisms in vivo (43)(44)(45)(46). Importantly, this osteoblast cell culture model provides a sensitive system to examine specific aspects of ER␣ on osteoblast activity uncomplicated by the presence of endogenous ERs.…”
Section: Er-dependent Gene Expression In Culturedmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). Therefore, these easily obtained and well characterized osteoblast cultures can be made estrogen responsive in vitro, replicating the hormone-sensitive status of osteoblasts that occur in more mature organisms in vivo (43)(44)(45)(46). Importantly, this osteoblast cell culture model provides a sensitive system to examine specific aspects of ER␣ on osteoblast activity uncomplicated by the presence of endogenous ERs.…”
Section: Er-dependent Gene Expression In Culturedmentioning
confidence: 99%
“…We chose to avoid possible complications from antibiotic toxicity, unknown effects from stable gene integration, and phenotypic drift by cells in continuous culture with our approach. Even so, it is difficult to know how the level of ER␣ expression in any transfected cell model compares with that in adult bone because, even in vivo, levels of ER␣ vary considerably with age and with anatomical bone location (43)(44)(45)(46). However, expression of ER␣ by transient gene transfection seemed appropriate and predictable, because the ability of estrogen to driven reporter gene expression by ERE was steroid- FIG.…”
Section: Fig 3 Er Associates With Runx2mentioning
confidence: 99%
“…Cells were scraped off the culture dishes and homogenized by freezing and thawing three times in cold isotonic extraction buffer [12]. Supernatant extracts were obtained by centrifugation at 14000xg for 5 min at 4°C in an Eppendorf micro-centrifuge.…”
Section: Creatine Kinase (Ck) Extraction and Assaymentioning
confidence: 99%
“…In human-derived cultured osteoblasts (hObs), we found that E 2 increased cell proliferation and CK specific activity in a gender specific manner [12] as a response marker for hormonal treatment beyond estrogen itself in cells containing the relevant receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation